Analisis Perlakuan Akuntansi Aset Biologis dan Penyusunan Laporan Keuangan Berdasarkan SAK EMKM pada Usaha Budidaya Ikan Nila Hananfishfarm di Kabupaten Subang - Anisa Maulida; Dwi Isti’adah; Syahril Riza Gilbran; Viena Dwi Aryani; Yati Nurhajati (INDO PUBLISHING, 2026)
Biological assets in the form of tilapia during the growth phase have dynamically changing values, thus requiring agricultural accounting treatment. However, most agricultural enterprises are farmers who operate as micro, small, and medium enterprises (MSMEs), and therefore need to understand accounting treatment based on SAK EMKM (Financial Accounting Standards for Micro, Small, and Medium Entities). This study aims to analyze the accounting treatment of biological assets and to prepare financial statements based on SAK EMKM at Hananfishfarm, a tilapia farming business in Subang Regency. The method used is descriptive qualitative with a case study approach, through observation, interviews, and documentation covering one production cycle from February 23 to May 12, 2025. The results show that Hananfishfarm has not yet carried out the recognition, measurement, presentation, or disclosure of biological assets in accordance with SAK EMKM; all costs of seed and feed were recorded as ordinary cash expenditures without capitalization, and no formal financial statements had been prepared. Based on the reconstruction carried out, the business's total assets should amount to Rp16,663,669, consisting of cash of Rp11,600,000 and biological assets of Rp5,063,669 that had never previously been presented, with net income for the period of Rp1,719,669. This study recommends the implementation of cost-capitalization-based recording for biological assets as well as accounting assistance for aquaculture MSME actors.